THE RELEVANCE OF LEARNING APPLIED ENGLISH FOR ACADEMICS TO FOSTER PROFESSIONALISM - Lubna Algadrie (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
Academics who are not competent in communication skills, particularly language skills, will develop less compared to those who are. Communication skills in general and language skills in particular will foster professionalism since professionals will spend less time doing and more time managing as experience grows. Professionalism grows from qualities that can be learned and developed as well as information learned and acquired. Negotiating skills will enable them to win deals more readily. Moreover, internet based realms of communications are mostly English speaking creations, which vary in terms of level of formality and choice of words. In this paper the writer shares her experience in materials preparations and a classroom-centered research done on a group of academics of non-English majors who came to ITS Language Centre to improve their English language competence for career development and further studies.